Killing commendatore [compact disc, unabridged] : a novel - Murakami, Haruki, 1949- (Random House Audio, 2018)
The much-anticipated new novel from the internationally acclaimed, best-selling author of 1Q84 and Colorless, Tsukuru Tazaki and His Years of Pilgrimage, this is an epic tour de force of love and loneliness, war and art, as well as a loving homage to The Great Gatsby, and a stunning work of imagination from one of the greatest writers.